Fairtrade e capital social: influências exógenas e suas contribuições para o desenvolvimento dos cafeicultores da cooperativa “Dos Costas” na região de Boa Esperança – MG - Aguiar, Bruno Henrique (2019)
Social capital has for decades been the target of research among researchers in the field of social sciences. Classics as Fukuyama (1996) and Putnam (1996) shows that regions with characteristics such as trust, cooperation and participation (among participants) would be more likely to develop. This study is the result of an interest in understanding the influence of Fair trade on the development of social capital, and the main objective was to investigate the influence of Fair trade on the development of social capital (trust, cooperation and participation) among Fair trade coffee growers associated with the Producers Cooperative of Special Coffee in Boa Esperança MG "DOS COSTAS". Observing at this proximity between social capital and development, this research sought evidence that the Fair trade philosophy and the participatory management encouraged by the system had a positive impact on the development of social capital among Fair trade coffee growers associated with the Producers Cooperative of Special Coffee in Boa Esperança MG "DOS COSTAS". The study brings in its approach social capital as an asset of local development, and dialogues about the need to build a collective project (among the actors). The study brings in its approach the social capital as an asset of local development, and dialogues about the need to build a collective project (among the participants). As a research strategy, the case study was adopted, which, in a qualitative approach, involved the investigation of social capital and the evidence of a development from the grassroots. For this purpose, the documentary analysis, the semistructured interviews with the selected actors, and the non-participant observation were used. The results indicate that the relationships of trust, cooperation and participation established between these participants were fundamental to the current stage of development of the group, it is still necessary to assert that the influence of the Fair trade philosophy and the participative management that this certification system requires had role and contribution to the current stage of development. The data collection evidenced the norms and principles of Fair trade certification, and social capital as factors that contributed to the development of coffee growers. The results indicate that the group's adhesion to the movement and Fair trade certification contributed to the development of the existing Social Capital among growers associated with the Producers Cooperative of Special Coffee in Boa Esperança MG "DOS COSTAS". Keywords: